ʺFormation of patriotic competence in the educational environment in institutions of professional higher education.ʺ - Kondrashkin, M. (Problems of Engineer-Pedagogical Education, 2024)
The war in Ukraine, the real threat of Ukraine's disappearance from the political map of the world, and the tumultuous political events of the coming months have radically changed our society. We have all changed in the face of war. The government and people of Ukraine have faced the need to unite, mobilize, surprise themselves and the world, and realize their identity, ethnic uniqueness and self-sufficiency, historical separateness, and their legitimate and inalienable right to be masters of their land. Unfortunately, the price is too high. We are now losing the most valuable thing that Ukraine has in its sons and daughters. At a time when the fate of the country is being decided, the relevance of patriotic education of young people is extremely high. Now, when there is a threat of our disappearance as a nation, there is an urgent need to develop patriotic competence in young people. After all, young people are our future and it depends on them what kind of future it will be. That is why in modern professional colleges, based on new approaches and methods of their implementation, there is a need to foster patriotism as a feeling and as a basic quality of personality. An effective way to successfully solve this problem is to create a patriotic educational environment in institutions of professional higher education. At the present stage of society's development, higher education institutions should give priority to patriotic education as an integral part of the educational process, foster love for their country, respect for other countries and peoples, cultivate love for Ukraine and its language, strengthen the sense of responsibility for Ukraine's independence, and the preservation of its material and spiritual values. The ideal is a harmoniously developed, conscious, highly professional citizen capable of self-development and self-improvement with a sense of great love for his or her native country.